Travel Sketches Of Malaya By Sir Frank Swettenham (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
The representation of Malaya (presently known as Malaysia) was evident through the works of both trained and amateur artists, among them Robert Smith, William Havell, James George, James Wathen and William J. Huggins. Besides these artists, representation of Malaya was also done by British officers who were sent to Malaya during the 19th century. One prominent figure was Frank Althelstane Swettenham (1850-1946), the first Resident General of the Federated Malay States (FMS) (1896-1901). This paper will examine some of his travel sketches of the Malayan landscape that inconspicuously reflected the British empire's ideology of industrialization, colonization, and exploration, and to the extreme extent of resource extraction and exploitation. Although it can be argued that the production of such imageries could be seen as a tool of anthropology or as a form of documentation and record, inevitably, such imageries were clues in understanding the changing landscapes and representation of landscape during the 19th century Malaya.